The Importance and Organization of Business Information Offered to Business Entities in Poland via the Global Internet Network - Dariusz Prokopowicz; Sylwia Gwoździewicz (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
Currently, in the era of information society and the development of information technology, information has become a particularly important element of social and professional functioning of both individual people and complex organizational structures and systems from which the modern world is built. In the context of running any business from the point of view of managing the organization, information can be a valuable commodity for the entrepreneur on a mobile, rapidly changing market. The development of techniques for processing and sharing information via the Internet is determined by many facilities for beneficiaries, customers and people using the information services offered by the Internet. In addition, for entities providing electronic information via the Internet, the possibility of a significant reduction of transaction costs of financial operations and electronic data transfer appears. On the other hand, the development of information technologies functioning on the Internet also involves the risk of loss or theft of information by unauthorized entities. This study describes key assumptions for the developmentand creation of a universal Internet portal offering information services for companies in the MSP sector that offers specialized information services provided via the Internet.